1984
DOI: 10.1139/g84-064
|View full text |Cite
|
Sign up to set email alerts
|

Linkage betwen the male sterility gene (ms1) and a translocation breakpoint in soybean, Glycine max

Abstract: SACKS, J. M., and K. SADANAGA. 1984. Linkage between the male sterility gene ( m s , ) and a translocation breakpoint in soybean, Glycine max. Can. J. Genet. Cytol. 26: 40 1 -404. The F2 distribution of male sterility ( m s and flower color ( M,,) in a cross between translocation 172-1 1-3 ( W, Wl Ms , Ms ,) and A77-139 (u, w , Ms ms , ) in soybean, Glycine ma,u (L.) Merr., was highly abnormal. Duplicate-deficient and 41-chromosome progenies constituted 32% of the Fz population. The M , , and ms I loci are loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Using standard linkage estimation methods, Palmer (1985) reported linkage between the breakpoint in Clark T/T and Y 11 (18.4 ± 0.4) and Df 2 (5.8 ± 0.2), and also between the breakpoint and Ms 1 (8.5 ± 1.5), Wm (36.8 ± 1.6), and W 1 (39.5 ± 2.0), thus placing the breakpoint between Ms 1 and Df 2 The values reported in our study for CLG 8 are in agreement with those reported by Palmer and Kaul (1983) and Palmer (1985), but different from Sadanaga and Grindeland (1984) and Sacks and Sadanaga (1984) These differences may be reflective of the different methods (F 2 and F 2:3 segregating data vs. microscope observations) used to obtain linkage data and the different generations of self‐pollination that occurred before the translocations were used in the different studies. Whereas Sadanaga and Grindeland (1984) and Sacks and Sadanaga (1984) used the translocations shortly after their isolation following mutagenesis, five generations of self‐pollination occurred before they were used in our study. Hence, their recombination values would have been subject more to any unknown instabilities or biases due to differential gametic or genotypic viabilities.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Using standard linkage estimation methods, Palmer (1985) reported linkage between the breakpoint in Clark T/T and Y 11 (18.4 ± 0.4) and Df 2 (5.8 ± 0.2), and also between the breakpoint and Ms 1 (8.5 ± 1.5), Wm (36.8 ± 1.6), and W 1 (39.5 ± 2.0), thus placing the breakpoint between Ms 1 and Df 2 The values reported in our study for CLG 8 are in agreement with those reported by Palmer and Kaul (1983) and Palmer (1985), but different from Sadanaga and Grindeland (1984) and Sacks and Sadanaga (1984) These differences may be reflective of the different methods (F 2 and F 2:3 segregating data vs. microscope observations) used to obtain linkage data and the different generations of self‐pollination that occurred before the translocations were used in the different studies. Whereas Sadanaga and Grindeland (1984) and Sacks and Sadanaga (1984) used the translocations shortly after their isolation following mutagenesis, five generations of self‐pollination occurred before they were used in our study. Hence, their recombination values would have been subject more to any unknown instabilities or biases due to differential gametic or genotypic viabilities.…”
Section: Resultssupporting
confidence: 91%
“…On the basis of the observation of chromosome number and constitution during meiosis, Sacks and Sadanaga (1984) reported linkage between W 1 and the breakpoint (2.0 ± 1.2) and Ms 1 and the breakpoint (18.4 ± 3.3), while Sadanaga and Grindeland (1984) reported linkage between the breakpoint and W 1 (1.9 ± 0.8) in KS172‐11‐3, and independent assortment with T and Y 10 Both studies placed the breakpoint distal to W 1 , and Sacks and Sadanaga (1984) placed the breakpoint between W 1 and Ms 1…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An individual heterozygous for a reciprocal translocation exhibits partial pollen and ovule sterility (40-60%), and this character defines the translocation breakpoint showing linkage with mutations of the two different linkage groups (Mahama and Palmer 2003). Associations between genetic markers and the translocation breakpoints were studied in soybean (Palmer and Kaul 1983;Sacks and Sadanaga 1984;Mahama et al 2002), lentil (Tadmor et al 1987) and pea (Berdnikov et al 1994). In grass pea, multiple interchanges have been detected among different chromosomes (Talukdar 2010), and a linked relationship between a flower colour mutation and translocation breakpoint has recently been elucidated (Talukdar 2011a).…”
Section: Introductionmentioning
confidence: 99%